2014
DOI: 10.2459/jcm.0b013e3283641bb8
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after primary angioplasty

Abstract: In patients with STEMI undergoing PPCI, high-volume hydration with normal saline or sodium bicarbonate administrated at the time of contrast media administration was not associated with any significant advantage in terms of CI-AKI prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Findings of a recent study have also shown that a higher saline HV (1085 ± 168 mL vs. 941 ± 148 mL) did not reduce the rate of CI-AKI (19% vs. 19.2%) following primary angioplasty, even with rapid hydration before the procedure [8]. These findings are similar to those from the present study in which similar patients underwent emergent procedures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Findings of a recent study have also shown that a higher saline HV (1085 ± 168 mL vs. 941 ± 148 mL) did not reduce the rate of CI-AKI (19% vs. 19.2%) following primary angioplasty, even with rapid hydration before the procedure [8]. These findings are similar to those from the present study in which similar patients underwent emergent procedures.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, a higher hydration volume (HV) has been associated with a significant trend towards a lower incidence of CIN [7]. However, no benefit existed in patients who were undergoing primary PCI and were administered more aggressive hydration [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies that included SB administration, 18 administered SB diluted with 5% dextrose in distilled water (D5%DW), and 4 did not specify the dilution of bicarbonate used 16 - 19 ; however, stabilized bicarbonate is only achieved with the addition of dextrose, so it can be assumed that this dilution was performed. The quantity of D5%DW for dilution differed among the studies; in 16 studies, 154 mL of bicarbonate (1,000 mEq/L) was diluted in 846 mL of D5%DW (studies 8 , 15 , 20 - 32 , 33 ); in the remaining studies, different mixtures of bicarbonate and D5%DW were used; the infusion speed was 1 to 3 mL/k/h within 1 to 12 h before the radiological procedure was performed and then between 6 and 12 h post-procedure ( Table 1 ). In six studies 20 , 21 , 23 , 27 , 29 , 32 , NAC was used along with the sodium bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome evaluated in 13 studies was the presence of CIN, defined as a 25% elevation in serum creatinine above the baseline or a 0.5-mg/dL increase during the first 48 hours after the contrast medium was administered 8 , 15 , 16 , 17 , 19 - 22 , 27 , 29 - 32 ; in seven studies, the same definition was used, but CIN was diagnosed up to 5 days post-contrast medium administration 23 , 25 , 26 , 28 , 33 - 35 ; the other two studies used the maximum increase in serum creatinine as an outcome measure 18 , 24 .…”
Section: Resultsmentioning
confidence: 99%